Harnessing Sustainable Healthcare through the Synergy of Artificial Intelligence (AI) and Blockchain Technologies in Kenya - Monethi, Tlhokomelo R.B. (WritingThreeSixty: Journal or Research and Creative Text, 2024)
Embarking on the frontier of healthcare transformation, the fusion of Artificial Intelligence (AI) and blockchain technologies in Kenya promises to redefine medical landscapes and serves as a beacon for sustainable development in a rapidly evolving digital era. The study employs a comprehensive approach, evaluating economic, social, and environmental dimensions to assess the impact of these technologies. Through a mixed-methods research strategy focusing on key healthcare projects, including AfyaRekod, Tambua Health, Ilara Health, PanaBIOS, and Sophie Bot, the research navigates challenges and highlights opportunities for transformative change. Key themes include; economic sustainability, emphasizing cost-effectiveness, resource optimization, and equitable growth. The study addresses social impact, focusing on healthcare access, patient experiences, and ethical considerations, and evaluates the environmental footprint, promoting strategies for minimizing energy use and adopting eco-friendly practices. Despite challenges in technology infrastructure and regulatory frameworks, the study underscores the transformative potential of AI and blockchain technologies. The findings provide crucial insights for informed decision-making, policy formulation, and the harmonious integration of technology with regulatory frameworks, ultimately contributing to a sustainable and balanced healthcare ecosystem.